DALGACIK TABANLI GÖRÜNTÜ SIKIŞTIRMA TEKNİĞİ - Emre Aksan; Süreyya Doğan (Havacılık ve Uzay Teknolojileri Dergisi, 2004)
Despite rapid progress in mass-storage density, processor speeds, and digital communication system performance, demand for data storage capacity and data transmission bandwidth continues to outstrip the capabilities of available technologies. Studies on image coding and compression techniques are still going on. The goal is to get the higher compression ratios with minimum loss of quality.